A new football hooliganism act necessary? - Mihaylova, Ekaterina; Mihaylov, Boris (Law Journal of New Bulgarian University, 2021)
This article examines the term â€œfootball hooliganismâ€ and its legal regulation. It analyses Bulgarian and European legislation on football hooliganism. It further discusses in details the 2018 amendments of the Protection of Public Order at Sports Events Act that employs new methods for tackling with this negative phenomenon.